Rice Mutants Lacking Starch Synthase I or Branching Enzyme IIb Activity Altered Starch Biosynthetic Protein Complexes - Crofts, Naoko; Iizuka, Yuriko; Abe, Natsuko; Miura, Satoko; Kikuchi, Kana; Matsushima, Ryo; Fujita, Naoko (Frontiers in Plant Science, 2018)
Amylopectin, the major component of starch, is synthesized by synergistic activity of multiple isozymes of starch synthases (SSs) and branching enzymes (BEs). The frequency and length of amylopectin branches determine the functionality of starch. In the rice endosperm, BEIIb generates short side chains of amylopectin and SSI elongates those branches, which can be further elongated by SSIIa. Absence of these enzymes greatly affects amylopectin structure. SSI, SSIIa, and BEIIb associate with each other and with other starch biosynthetic enzymes although SSIIa is low activity in japonica rice. The aim of the current study was to understand how the activity of starch biosynthetic enzyme complexes is compensated in the absence of SSI or BEIIb, and whether the compensatory effects are different in the absence of BEIIb or in the presence of inactive BEIIb. Interactions between starch biosynthetic enzymes were analyzed using one ss1 null mutant and two be2b japonica rice mutants (a mutant producing inactive BEIIb and a mutant that did not produce BEIIb). Soluble proteins extracted from the developing rice seeds were separated by gel filtration chromatography. In the absence of BEIIb activity, BEIIa was eluted in a broad molecular weight range (60–700 kDa). BEIIa in the wild-type was eluted with a mass below 300 kDa. Further, majority of inactive BEIIb co-eluted with SSI, SSIIa, and BEI, in a mass fraction over 700 kDa, whereas only small amounts of these isozymes were found in the wild-type. Compared with the be2b lines, the ss1 mutant showed subtle differences in protein profiles, but the amounts of SSIIa, SSIVb, and BEI in the over-700–kDa fraction were elevated. Immunoprecipitation revealed reduced association of SSIIa and BEIIb in the ss1 mutant, while the association of BEIIb with SSI, SSIIa, SSIVb, BEI, and BEIIa were more pronounced in the be2b mutant that produced inactive BEIIb enzyme. Mass spectrometry and western blotting revealed that SSI, SSIIa, SSIIIa, BEI, BEIIa, starch phosphorylase 1, and pullulanase were bound to the starch granules in the be2b mutants, but not in the wild-type and ss1 mutant. These results will aid the understanding of the mechanism of amylopectin biosynthesis.